SUPERVISI PENDIDIKAN ISLAM ADAPTIF: STRATEGI KEPEMIMPINAN VISIONER DI ERA DIGITAL DAN TANTANGAN REVOLUSI INDUSTRI 5.0 - Wardhani, Suryaningtiyas Puspa; Salsabila, Naila Rahma; Apriyadi, Ridho; Subandi, Subandi; Dermawan, Oki (Jurnal Manajemen Pendidikan, 2025)
The traditional paradigm of supervision—previously administrative and inspection-oriented—must now evolve into a model that is collaborative, responsive, and evidence-based. This article explores how Islamic educational supervision practices can be adapted through visionary leadership that integrates digitalization, Islamic values, and 21st-century competencies. The research method employed is a systematic literature review and conceptual analysis of English and Indonesian scientific publications from 2020–2025 discussing educational supervision, Islamic educational leadership, digital transformation, and the Industry 5.0 concept. Content analysis techniques were used to extract major themes and formulate a conceptual framework for adaptive supervision. The findings indicate that visionary leadership capable of formulating a “human-centric” and digital vision, supporting the digitalization of supervisory processes, and integrating Islamic values within technological guidelines is a key factor for successful adaptive supervision. Supervision designed through collaborative teacher engagement, peer-supervision, and real-time data utilization accelerates the transformation of learning practices.